Pontoscolex corethrurus (Annelida: Oligochaeta) indicador de la calidad del suelo en sitios de Eucalyptus grandis (Myrtacea) con manejo tumba y quema - Uribe, Sheila (2012)
Pontoscolex corethrurus (Annelidae: Oligochaeta) soil quality indicator in Eucalyptus grandis (Myrtacea) sites with slash and burn management. Soil burning has been used in agricultural and forestry systems as a fundamental technique to clean the land and add some nutrients to the soil. In addition, earthworms are known to promote various soil functions since they contribute to aeration and organic matter and nutrients availability to other soil organisms. This study evaluated the effects of tropical forest crops management with presence-absence of Eucalyptus grandis on earthworm population in Huimanquillo, Tabasco, Mexico. Three sites (average area of 1-1.5ha each) with different management conditions were considered for soil and earth- worm sampling (two depths and six replicates): without vegetation (SV) and recent slash-burned (38 days), forest crops of five years of production of E. grandis (Euc), and secondary vegetation of 15 years (Acah). Soil physico-chemical properties (apparent density, humidity, texture, pH, Ntot, OM, P, K, cationic capacity) were also evaluated, and earthworms were collected at the end of the rainy season (august-october 2007). We found that the sites soil is an acrisol acid, with pH 3.0-4.5 in the first 30cm depth. Organic matter content (OM) and total nitrogen (Ntot) in the recently burned sites were significantly lower (6-8% y 0.19-0.22%, respectively) than in sites with vegetation (OM=9-11%; el Ntot=0.27-0.33%). Only one species (P. corethrurus) was found in all the sampled areas, where most of the individuals were at juvenile stage (80%). The highest densities and biomass were found in Euc. treatment (166.4ind/m2 y 36.8g/m2) followed by Acah (138.7ind/m2 y 19.1g/m2 respectively), while the SV treatment showed of about an 80% reduced earthworm populations when compared to other treatments. Even though 15 years have passed over the secondary vegetation (Acah) still some perturbations were observed as the low abundance of the oligochaeta group. We concluded that the management used to culture E. grandis produces negative effects over the abundance and diversity of earthworms and soil nutrient availability.